Effects of Depression Screening on Quality of Life after Diagnosis of Acute Coronary Syndrome, Single Center Experience (Medical Forum Monthly, 2022)
Objective: To verify whether analytically finding depression in survivors of an ACS increases the standard of life and depression compared to the accustomed concern.Study Design: Randomized controlled trial study.Place and Duration of Study: This study was conducted at the DG Khan Medical College, DG Khan from September 03 2021 to 02 March 2022.Materials and Methods: 450 ACS patients were enrolled. ACS patients who had been admitted to the hospital in the past 2 to 12 months without a prior history of depression were eligible for the study. The analyses were conducted based on intention-to-treat.Results: Patients with ACS received (1) systematic depression screening utilizing the eight-item Patient Health Questionnaire, with notification of crucial care physicians and stipulation of centralized, patient-performed, gradual depression care for those with depression, Patients with a positive screening result (8-Item Patient Health Questionnaire score >10: Screen, notify, and treat); 2) systematic depression screening with notification of primary healthcare providers for those with a positive finding result (Screen and notify); and (3) normal care with no finding. A quality attuned life-year change was the crucial upshot. The second effect was the number of days with no depression. Patients' interviews and hospital minutes were used to evaluate adverse effects and death.Conclusion: Organized depression screening with or lacking depression cure had no influence on quality-adjusted life years or tribulations in ACS patients with no record of depression.